Adoption and adherence to chronic obstructive pulmonary disease GOLD guidelines in a primary care setting. (April 2019) - Surani, Salim; Aiyer, Akshar; Eikermann, Stephen; Murphy, Timothy; Anand, Pranav; Varon, Joseph; Vanderheiden, David; Khan, Alamgir; Guzman, Antonio
Objectives: Over 380 million people in the world live with chronic obstructive pulmonary disease, and it is the third leading cause of death in the United States. Despite updated guidelines, there may be significant variations in diagnosis and management of chronic obstructive pulmonary disease at a primary care level. The aim of the study was to examine primary care physician management of chronic obstructive pulmonary disease in two community clinics. Methods: After approval from the Institutional Review Board, a retrospective chart review was done among all patients with the diagnosis of chronic obstructive pulmonary disease in two community clinics. Baseline demographics, utilization of spirometry, exacerbation history and home oxygen use were also obtained. Results: Chart reviews of 101 patients were completed (52 male and 49 female) in two outpatient primary care provider offices (Office A: 66 patients and Office B: 35 patients). None of the patients had validated measures of dyspnoea such as CAT or mMRC scores. Only 21% (22/101) of the patients had formal pulmonary function test testing done, and of those who had pulmonary function tests, 31.5% of patients were incorrectly diagnosed and mislabelled as chronic obstructive pulmonary disease. Pharmacotherapy for chronic obstructive pulmonary disease was not in alignment with GOLD guidelines, with only 42% of patients on an inhaler regimen that included a long-acting muscarinic antagonist. Conclusion: There is suboptimal use of pulmonary function test in a primary care setting for diagnosis of chronic obstructive pulmonary disease and substantial errors in diagnosis. There is virtually no use routinely of validated symptom scales for diagnosis of chronic obstructive pulmonary disease. There is substantial variance in pharmacotherapy, and regimens routinely do not follow GOLD guidelines.